2015
DOI: 10.1002/elps.201400544
|View full text |Cite
|
Sign up to set email alerts
|

High throughput multiorgan metabolomics in the APP/PS1 mouse model of Alzheimer's disease

Abstract: Metabolomics has demonstrated a great potential for the study of pathological mechanisms occurring in brain from Alzheimer's disease patients and transgenic models. However, its application to peripheral samples is not so common, although it can provide interesting information about systemic abnormalities underlying to disease. This work represents the first metabolomic investigation of multiple peripheral organs (liver, kidney, spleen, and thymus) from the APP/PS1 mice by using a high-throughput approach base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 76 publications
4
22
0
Order By: Relevance
“…Furthermore, these findings were then validated using orthogonal hyphenated approaches, such as UHPLC-MS [36,37], GC-MS [37,38], and CE-MS [39], demonstrating the reliability of direct MS-based metabolomics. This DIMS platform was latterly adapted for the analysis of other biological matrices, such as urine [40], brain [41], peripheral organs (i.e., liver, kidney, thymus, spleen) [42], as well as muscle, hepatopancreas, and antennal gland [43], providing very valuable results to accomplish a preliminary metabolomic screening prior to the application of other complementary techniques. Lin et al also described the application of DIMS-based metabolomics to investigate the characteristic neurochemical profile of the CRND8 transgenic mice.…”
Section: Application Of Dims Metabolomicmentioning
confidence: 99%
“…Furthermore, these findings were then validated using orthogonal hyphenated approaches, such as UHPLC-MS [36,37], GC-MS [37,38], and CE-MS [39], demonstrating the reliability of direct MS-based metabolomics. This DIMS platform was latterly adapted for the analysis of other biological matrices, such as urine [40], brain [41], peripheral organs (i.e., liver, kidney, thymus, spleen) [42], as well as muscle, hepatopancreas, and antennal gland [43], providing very valuable results to accomplish a preliminary metabolomic screening prior to the application of other complementary techniques. Lin et al also described the application of DIMS-based metabolomics to investigate the characteristic neurochemical profile of the CRND8 transgenic mice.…”
Section: Application Of Dims Metabolomicmentioning
confidence: 99%
“…Consistently, a recent study conducting metabolomic investigation of multiple peripheral organs (liver, kidney, spleen, and thymus) from this transgenic mice at 6 months of age demonstrated that these organs suffered significant metabolic abnormalities, with the liver being the most affected organ by oxidative stress (Gonzalez‐Dominguez et al . 2015a). Together this supports our observation that inflammation can occur in AD liver.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, several recent studies investigating metabolites revealed significant metabolic changes in the liver and other peripheral organs (Gonzalez‐Dominguez et al . ,b). Our previous study also found AD transgenic mice were susceptible to osteoporosis of the femoral bones, which was ameliorated by high‐fat diet (HFD)‐induced body weight gain (Peng et al .…”
mentioning
confidence: 99%
“…Alternatively, other peripheral organs from the APP×PS1 model have also been investigated to assess the possible systemic nature of AD, including the liver, kidneys, spleen and thymus [32]. In this work, authors found significant impairments associated with oxidative stress, lipid dyshomeostasis and imbalances in energy metabolism, among other processes, results which were subsequently validated by using a metabolomic multiplatform based on the combination of LC and GC coupled to MS [33,34].…”
Section: Application Of Direct Mass Spectrometry-based Metabolomics Tmentioning
confidence: 94%